Immunoregulation by Artemisinin and Its Derivatives: A New Role for Old Antimalarial Drugs - Qiu, Feifei; Liu, Junfeng; Mo, Xiumei; Liu, Huazhen; Chen, Yuchao; Dai, Zhenhua (Frontiers in Immunology, 2021)
Artemisinin and its derivatives (ARTs) are known as conventional antimalarial drugs with clinical safety and efficacy. Youyou Tu was awarded a Nobel Prize in Physiology and Medicine due to her discovery of artemisinin and its therapeutic effects on malaria. Apart from antimalarial effects, mounting evidence has demonstrated that ARTs exert therapeutic effects on inflammation and autoimmune disorders because of their anti-inflammatory and immunoregulatory properties. In this aspect, tremendous progress has been made during the past five to seven years. Therefore, the present review summarizes recent studies that have explored the anti-inflammatory and immunomodulatory effects of ARTs on autoimmune diseases and transplant rejection. In this review, we also discuss the cellular and molecular mechanisms underlying the immunomodulatory effects of ARTs. Recent preclinical studies will help lay the groundwork for clinical trials using ARTs to treat various immune-based disorders, especially autoimmune diseases.